Evolution of planted forests between 1986 and 2017: the Brazilian case of Peçanha, Minas Gerais - Barbosa, Rodney Alves; Braga, Gustavo Bastos; Valverde, Sebastião Renato; Vilela, Katia de Fatima; Queiroz, Camila Savastano de; Souza, Patrícia Barbosa de; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
The massif forest market has been gaining prominence in Brazil, due to its participation in the economy. In Brazil, Minas Gerais State represents the largest planted forest area in the country and Peçanha municipality stands out for its wood production as well as for the insertion of its rural producers in the cellulose industry productive chain. This research aimed at mapping the evolutions of the planted forests in Peçanha, MG, from 1986 to 2017, presenting the forests planted by the private companies as well as the ones planted by the rural producers, integrated or not to the cellulose industry. The methodology of the research assumes an exploratory and a documental character, meaning a study case in which primary data were used obtained through interviews, and secondary data about the forest sector of the municipality, such as maps of the soil use and occupation, obtained from the MapBiomas Project of the IBGE and reports made by the cellulose industry. The results showed that there was an increase in the planted forest area and a decrease of grazing and agricultural areas, as well as an increase in wood production for cellulose industry and for the vegetal charcoal production, destined to the steelwork sector. It was concluded that the rural producer has been expanding the forestry areas, mainly over grazing and agricultural areas.
Keywords: Rural producers; Cellulose industry; Forest fomenting